2013
DOI: 10.1111/avsc.12046
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and phosphorus fertilizer regime affect jarrah forest restoration after bauxite mining in Western Australia

Abstract: Question Removal of vegetation and disturbance of the soil profile during mining reduce nutrient pools available for plants during mine site restoration. Thus, fertilizer is needed to replace the loss of nutrients available to support vegetation establishment. Yet the application of fertilizer can promote the establishment of competitively dominant species to the exclusion of others, particularly in low‐fertility ecosystems. Here, we test effects of fertilizer application rates on the establishment of jarrah f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
43
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 42 publications
7
43
1
Order By: Relevance
“…We found that species richness, density and cover of weeds and the density of native ephemerals increased with increasing P. This result is consistent with other studies that have reported higher rates of fertiliser to increase species richness, cover and density of exotic annuals (e.g. Prober and Wiehl, 2012;Daws et al, 2013) and native ephemeral species (Daws et al, 2013). However, for these groups, cover and density increased to a lesser extent at the highest P-application rate when large legumes were seeded, i.e.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…We found that species richness, density and cover of weeds and the density of native ephemerals increased with increasing P. This result is consistent with other studies that have reported higher rates of fertiliser to increase species richness, cover and density of exotic annuals (e.g. Prober and Wiehl, 2012;Daws et al, 2013) and native ephemeral species (Daws et al, 2013). However, for these groups, cover and density increased to a lesser extent at the highest P-application rate when large legumes were seeded, i.e.…”
Section: Discussionsupporting
confidence: 92%
“…the premise that additional legumes may increase tree growth due to higher N-availability was not supported. Although the sampling regime for soil nutrients was low (6 sample locations plot À1 in 2006), these results are consistent with other studies that have also shown low availability of N in restored jarrah forest soils (Daws et al, 2013;Standish et al, 2008). While large legumes had no effect on tree growth in our study, the competitive environment resulting from high legume densities can in fact reduce tree growth in both restored sites and forestry plantations (Turvey et al, 1983;Koch, 1987;Forrester et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations